2011
DOI: 10.1007/s10725-011-9597-7
|View full text |Cite
|
Sign up to set email alerts
|

Auxin stability and accumulation during in vitro shoot morphogenesis influences subsequent root induction and development in Eucalyptus grandis

Abstract: Recent results showed that after 16 months in the field, micropropagated eucalyptus plants have an inferior root system to cuttings. Such differences may be due to the plant growth regulators supplied during the culture stages of standard protocols, which are targeted at optimising plantlet yields and not root quality. This study investigated such a proposal, focusing on auxins in an easyto-root clone. Initial results showed that the auxin provided in the standard protocol (NAA for multiplication and IBA for e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 38 publications
(53 reference statements)
1
27
0
1
Order By: Relevance
“…Optimally-treated eucalypt shoots often produce a mean of about four adventitious roots but individual shoots can produce higher root numbers [3,4,9,17,[19][20][21][22][23][24]47,48]. These roots could have emerged along more than four radii at the same level within the shoot.…”
Section: Discussionmentioning
confidence: 99%
“…Optimally-treated eucalypt shoots often produce a mean of about four adventitious roots but individual shoots can produce higher root numbers [3,4,9,17,[19][20][21][22][23][24]47,48]. These roots could have emerged along more than four radii at the same level within the shoot.…”
Section: Discussionmentioning
confidence: 99%
“…Chromatographic methods can provide excellent hormone separation and, when coupled with mass spectrometry (MS), allow quantification of compounds from multiple hormone classes in the same sample [69,106]. These methods have greatly improved endogenous auxin identification in forestry species [107][108][109][110].…”
Section: Chromatography and Mass Spectrometrymentioning
confidence: 99%
“…IAA levels in the cutting base and apex remained constant and were similar to those in intact seedlings, indicating that root initiation can occur without an increase in the IAA levels in the root regeneration zone [45]. Differences in auxin transport capacity may contribute directly to success in the rhizogenesis process [108], with applied auxin possibly being transported more rapidly in easy-to-root plants [141].…”
Section: Auxin Dynamics During Vegetative Propagationmentioning
confidence: 99%
“…Furthermore, most eucalypt micropropagation protocols, including that of Mokotedi et al (2010), utilise one or more auxin analogues to induce roots in vitro (Jones and Van Staden, 1997;Watt et al, 2003). However, Nakhooda et al (2011) reported that the choice of auxin, along with its relative stability and concentration used in vitro, influences several aspects of root development, including post-acclimatisation root architecture. Those authors found that IAA (indole-3-acetic acid) was integral to the rooting process, regardless of the presence of other auxin analogues, such as IBA (indole-3-butyric acid) or sensitivity to exogenous auxin.…”
Section: Introductionmentioning
confidence: 99%